Wardisease - Magescas, Marie (France, 2010)
On December 10, 1948, the General Assembly of the United Nations adopted and proclaimed the Universal Declaration of Human Rights. Five of these UN member countries are today the biggest arms dealers in the world. "WARdisease" explores the hipocrisy of firearm-related legislation. Men, women and children. Run, cry, fall, die, be armed. And start again.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films